Understanding University Enterprise Collaboration for Disaster Resilience in South-East Asia - Tucker, Rebeka Catherine (Archīum Ateneo, 2023)
Purpose This paper is part of the ERASMUS+-funded Strengthening University Enterprise Collaboration for Resilient Communities in Asia (SECRA) project. This study aims to map collaborative architecture between partner universities and the public/private sectors to provide a contextualised collaboration framework for disaster resilience (DR) in South-East Asia. Design/methodology/approach Documentary reviews were conducted in partner countries to establish the current context of university enterprise collaborations (UEC) in South-East Asia. A concept-centric approach permitted the synthesis of concepts from each country review, allowing for comparisons between collaborative practices that impact the success of DR collaborations. Findings The review identified that funding, continuity, long-term strategic plans and practical implementation are lacking in partner countries. However, each country demonstrated good practices and identified enablers and barriers that impact DR collaborations. Research limitations/implications The synthesis revealed a lack of a practical understanding of real-world barriers. Further research is needed to understand real-world experiences in DR collaborations and to provide insights into barriers, enablers and good practices in DR collaborations. Gaining an “on-the-ground” perspective will provide detailed insights and the feasibility of implementation. Practical implications The findings provide the foundations for developing a heuristic UEC framework that can inform policies and practices for DR in partner countries. Social implications The findings can inform various stakeholder policies and practices and promote the exchange of ideas between stakeholders to enhance DR in South-East Asia. Originality/value The results are relevant within the South-East Asian, as governments have intensified the adoption of measures to encourage UEC for DR.